2005
DOI: 10.1021/jo048161z
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorocarbene Addition to Cyclopropenes:  A Computational Study

Abstract: Reaction paths for addition of dichlorocarbene to 1,2-disubstituted cyclopropenes were calculated using hybrid density functional theory (B3LYP/6-31G) in the gas phase and in the presence of a continuum solvation model corresponding to acetonitrile. In both the gas phase and acetonitrile, :CCl2-cyclopropene addition follows an asymmetric, non-least-motion approach. Barriers to addition range from 0 to 2 kcal/mol. The reactions proceed in concerted fashion in both the gas phase and solution to yield 1,3-dienes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
49
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 44 publications
9
49
0
1
Order By: Relevance
“…Summing the trajectories that either terminate as or proceed through 2a , the ratio of bicyclobutane‐mediated trajectories to butadiene‐forming trajectories (i.e., Brinker's product ratio: ( 2a + 4a )/ 5a ) is 323/69 = 4.7. Therefore, molecular dynamics has successfully modeled Brinker's experimental product ratio of 4:1, which supports our previous proposal: CCl 2 addition to cyclopropene is controlled by reaction dynamics.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Summing the trajectories that either terminate as or proceed through 2a , the ratio of bicyclobutane‐mediated trajectories to butadiene‐forming trajectories (i.e., Brinker's product ratio: ( 2a + 4a )/ 5a ) is 323/69 = 4.7. Therefore, molecular dynamics has successfully modeled Brinker's experimental product ratio of 4:1, which supports our previous proposal: CCl 2 addition to cyclopropene is controlled by reaction dynamics.…”
Section: Resultssupporting
confidence: 85%
“…Our previous computational study of CCl 2 + cyclopropene ( 1a , and also 1b and R = CH 3 , CH=CH 2 ) showed Brinker's major (bicyclobutane 2a ) and minor (butadiene 5a ) products to derive from the same TS in a concerted manner . Specifically, we did not find a zwitterionic intermediate on the potential energy surface of CCl 2 + cyclopropene, and the paths to form 2a and 5a diverged after the TS .…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Two-step mechanisms for carbene addition to olefins were discussed previously by Jones and Moss. [4] While the recent computational investigation of Merrer and Rablen [48] does not lend support to the existence of intermediates in the reaction of CCl 2 with cyclopropenes, [49][50][51][52] the rearrangements of vinyl-substituted cyclopropylcarbenes are best rationalized by a diradicaloid intermediate. [53,54] The computational analysis of the ethylene + CF 2 reaction by Bernardi et al [55] at the (4,4)-CASSCF/6-31G* level suggested a two-step mechanism with a diradical intermediate having a barrier to ring closure of only 0.2 kcal mol À1 .…”
mentioning
confidence: 99%
“…We previously showed the formation of butadiene to result from dynamic effects. 25,26 isomerization of 1a to 6a in an Ar matrix. 19 Path E outlines stepwise carbene addition to 6a followed by rearrangement and loss of N 2 , whereas path F is the concerted analogue.…”
Section: ■ Introductionmentioning
confidence: 99%